Cubic interpolated pseudo particle (CIP) - lattice boltzmann scheme for the simulation of natural convection heat transfer [electronic resource] - 455958 Mohd. Rosdzimin Abdul Rahman; Nor Azwadi Che Sidik, supervisor; Fakulti Kejuruteraan Mekanikal (2008)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2008